El tiempo pretérito en el castellano andino de niños bilingües de Ayacucho - Esquivel Villafana, Jorge (2020)
This work describes and characterizes the use of perfect and imperfect past verb forms, with their respective modal variants in the Spanish spoken by quechua-spanish bilingual children from La Mar district (Ayacucho).